Information and trading targets in a dynamic market equilibrium - Choi, Jin Hyuk; Larsen, Kasper; Seppi, Duane J. (Journal of Financial Economics, 2019)
This paper describes equilibrium interactions between dynamic portfolio rebalancing given a private end-of-day trading target and dynamic trading on long-lived private information. Order-splitting for portfolio rebalancing injects multifaceted dynamics in the market. These include autocorrelated order flow, sunshine trading, endogenous learning, and short-term speculation. The model has testable implications for intraday patterns in volume, liquidity, price volatility, order-flow autocorrelation, differences between informed-investor and rebalancer trading strategies, and for how these patterns comove with trading-target volatility and other market conditions.